Al-Zarnuji and Al-Attas’ thoughts of education: the analysis and discussion - Husein, Saddam; Nik Abdullah, Nik Md. Saiful Azizi; Nasution, Tetty Khairani (Kulliyyah of Languages and Managements (KLM), International Islamic University of Malaysia Pagoh Campus, 2021)
This paper aims to analyze and to discuss al-Zarnuji and al-Attas’ thoughts of education. The author chose these two scholars based on their educational concepts and philosophy which have huge implications toward Islamic education worldwide. This is a library research with descriptive qualitative analysis. The data intended was collected from the primary and secondary sources, original works of both scholars and some other related studies by previous researchers. The findings confirm that both scholars' concepts of education have similarities in the educational goals and classification of knowledge and differences in the educational philosophy, methods and level of education targeted. More specifically, al-Attas uses the philosophical approach as the basis in looking at education; it can be seen from the way he defines knowledge, man, and education. While al-Zarnuji used the basis of experience and practice in viewing education, for instance, the way he formulated knowledge and intention, selecting teachers and companions, and also in determining the time for study. Furthermore, the concept of education offered by al-Zarnuji seems to be suitable for the Pesantren system as a traditional Islamic school which relies heavily on the figure of a ulama’ (kyai) and good circumstances of the boarding school system. Meanwhile, al-Attas concept of education is very compatible with Islamic higher education which the concept of education offered is related to the university level (kulliyah al-Jam'iyah).It can be seen from his consideration on universality of perfect man (insan kamil), who is able to stand alone to consider and to decide which one is right (Haqq)and which one is falsehood or futile (bathil). Shortly, these two figures complement each other, Zarnuji offers the concept of early education and al-Attas offers the concept of higher education